Changes in the Chemical Composition and Decay Resistance of Thermally-Modified Hevea brasiliensis Wood - Severo, Elias Taylor Durgante; Calonego, Fred Willians; Sansígolo, Cláudio Angeli; Bond, Brian (Public Library of Science (PLoS), 2016)
In this study the effect of thermal treatment on the equilibrium moisture content, chemical composition and biological resistance to decay fungi of juvenile and mature Hevea brasiliensis wood (rubber wood) was evaluated. Samples were taken from a 53-year-old rubber wood plantation located in Tabapuã, Sao Paulo, Brazil. The samples were thermally-modified at 180°C, 200°C and 220°C. Results indicate that the thermal modification caused: (1) a significant increase in the extractive content and proportional increase in the lignin content at 220°C; (2) a significant decrease in the equilibrium moisture content, holocelluloses, arabinose, galactose and xylose content, but no change in glucose content; and (3) a significant increase in wood decay resistance against both Pycnoporus sanguineus (L.) Murrill and Gloeophyllum trabeum (Pers.) Murrill decay fungi. The greatest decay resistance was achieved from treatment at 220°C which resulted in a change in wood decay resistance class from moderately resistant to resistant. Finally, this study also demonstrated that the influence of thermal treatment in mature wood was lower than in juvenile wood.